Trend and Mapping of Digital Interactive Media Based Differentiated Instruction: A Systematic Literature Review: English - Nurul Fatima; Novi Ratna Dewi; Dadi Rosadi (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
The development of digital technology has encouraged the use of interactive media in learning to accommodate the diversity of student characteristics. Differentiated learning has become a relevant approach because it emphasizes the adaptation of learning content, processes, and products according to student needs. The purpose of this study is to examine the trends in research publications on interactive digital media for differentiated learning in the period 2016-2026. The article search method used a systematic literature review with PRISMA standards through a search of scopus data. A total of 383 articles were analyzed using vos viewers and the analytical database on scopus. The results showed that the trend of differentiation topics has increased, especially in the context of digital technology utilization. Countries such as the United States, Indonesia, and China are the main contributors to publications on this topic. The dominant keywords that frequently appear reflect a focus on digital technology, games, virtual reality, e-learning, and artificial intelligence. In addition, journals with the highest citations show the importance of student engagement, the use of web-based learning, learning management systems (LMS), mobile applications, gamification, and virtual reality in differentiated learning. The findings of this study are interactive digital media for differentiated learning integrated with digital technology in the form virtual reality, LMS, websites, AI, E-learning, and mobile applications